Loss of ATRX confers DNA repair defects and PARP inhibitor sensitivity - Garbarino, Jennifer; Eckroate, Jillian; Sundaram, Ranjini K.; Jensen, Ryan B.; Bindra, Ranjit S. (Translational oncology, 2021)
•Drug screen shows that ATRX KO leads to PARP inhibitor sensitivity in glioma cells.•PARPi leads to greater levels of replication stress in ATRX KO cells than WT.•IDH1 R132H and ATRX KO have similar levels of PARP inhibitor sensitivity.•ATRi and PARPi have greater synergy in ATRX KO cells. Alpha Thalassemia/Mental Retardation Syndrome X-Linked (ATRX) is mutated frequently in gliomas and represents a potential target for cancer therapies. ATRX is known to function as a histone chaperone that helps incorporate histone variant, H3.3, into the genome. Studies have implicated ATRX in key DNA damage response (DDR) pathways but a distinct role in DNA repair has yet to be fully elucidated. To further investigate the function of ATRX in the DDR, we created isogenic wild-type (WT) and ATRX knockout (KO) model cell lines using CRISPR-based gene targeting. These studies revealed that loss of ATRX confers sensitivity to poly(ADP)-ribose polymerase (PARP) inhibitors, which was linked to an increase in replication stress, as detected by increased activation of the ataxia telangiectasia and Rad3-related (ATR) signaling axis. ATRX mutations frequently co-occur with mutations in isocitrate dehydrogenase-1 and -2 (IDH1/2), and the latter mutations also induce HR defects and PARP inhibitor sensitivity. We found that the magnitude of PARP inhibitor sensitivity was equal in the context of each mutation alone, although no further sensitization was observed in combination, suggesting an epistatic interaction. Finally, we observed enhanced synergistic tumor cell killing in ATRX KO cells with ATR and PARP inhibition, which is commonly seen in HR-defective cells. Taken together, these data reveal that ATRX may be used as a molecular marker for DDR defects and PARP inhibitor sensitivity, independent of IDH1/2 mutations. These data highlight the important role of common glioma-associated mutations in the regulation of DDR, and novel avenues for molecularly guided therapeutic intervention.